UHF RFID proof of concept (POC) with open-source ILS at Universiti Sains Malaysia (USM) Libraries. Issue 2 (7th April 2015) - Khor, JingHuey; Ismail, Widad; Md Rashid, Mohd Nasir; Wan Ismail, A. Akla; Omar, Muhammad Qayum; Mohd Zanal, Farah Hazwani
Abstract : Purpose: – Universiti Sains Malaysia (USM) uses different detection technologies and integrated library systems (ILS) at its four libraries located at different sites. Hence, ubiquitous data management system is required in the four libraries to enable real-time data sharing and tracking among the libraries. The paper aims to discuss these issues. Design/methodology/approach: – Proof of concept is used to verify the performance of integration between different detection technologies including barcode, high frequency (HF) and ultra high frequency (UHF) radio frequency identification (RFID) as well as Integrated Library Management Utility (ILMU) and Koha ILSs. Five pilot tests are performed to investigate the speed of the borrowing and returning transactions, the efficiency of security gate to detect non-borrowed items, and the reliability of the ubiquitous data management system. Findings: – The HF RFID technology and the proprietary library system have been used in many libraries. The current study proves that the integration of the UHF RFID technology and the Koha open-source ILS, which is named as Total Open-Source Library Automation Solution, can be a novel solution and can serve as a guide for other libraries. Originality/value: – In the current phase of library data management system, it is common to integrate various technologies in improving the efficiency of the library system. But, the combination of Koha with UHF RFID into a single ILS for intra-library automation system has not been proven. This shows the importance of the proposed proven proof of concept that proves such integration is suitable to be implemented at USM libraries and other libraries.